1998
DOI: 10.1016/s0378-4371(98)00326-4
|View full text |Cite
|
Sign up to set email alerts
|

Continuum model for radial interface growth

Abstract: A stochastic partial differential equation along the lines of the Kardar-Parisi-Zhang equation is introduced for the evolution of a growing interface in a radial geometry. Regular polygon solutions as well as radially symmetric solutions are identified in the deterministic limit. The polygon solutions, of relevance to on-lattice Eden growth from a seed in the zero-noise limit, are unstable in the continuum in favour of the symmetric solutions. The asymptotic surface width scaling for stochastic radial interfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…We mention that, aside from some early works [101,102,103], and more recently [104], there has been little direct effort on numerical integration of 2d KPZ equation in polar coordinates; see, too [105,106,107]. Indeed, all work on this subclass, aside from radial Eden model simulations [108,109], have resorted to difficult, somewhat frustrating pt-pt simulations of various KPZ/DPRM models [110,65] in what is, effectively, constrained wedge geometries.…”
Section: An Homage To Psmentioning
confidence: 99%
“…We mention that, aside from some early works [101,102,103], and more recently [104], there has been little direct effort on numerical integration of 2d KPZ equation in polar coordinates; see, too [105,106,107]. Indeed, all work on this subclass, aside from radial Eden model simulations [108,109], have resorted to difficult, somewhat frustrating pt-pt simulations of various KPZ/DPRM models [110,65] in what is, effectively, constrained wedge geometries.…”
Section: An Homage To Psmentioning
confidence: 99%
“…In order to construct radial growth equations one may invoke the reparametrization invariance principle [21,22], as has already been done a number of times [10,11,[13][14][15][16]. In the case of white and Gaussian fluctuations, the d-dimensional spherical noise is given by…”
Section: Radial Random Depositionmentioning
confidence: 99%
“…The shape of radial interfaces was illustrated by means of numerical simulations in [16] and [17]; their deterministic evolution is analogous to that of an elliptic interface of null eccentricity, see Sec.…”
Section: Radial Geometrymentioning
confidence: 99%
“…Subsequent works were devoted to the radial (1 + 1d) KPZ equation [16,17,18], the radial (1 + 1d) and spherical (2 + 1d) Mullins-Herring (MH) equa-tion [19,20], and the general reparametrization invariant formulation of stochastic growth equations [21]. An analytical approach to these equations [18] showed that for short spatial scales and time intervals the dynamics of radial interfaces was equivalent to that of the planar case; however, long time intervals yielded a different output.…”
Section: Introductionmentioning
confidence: 99%